Development of a Multi-Bed Catalytic Heat Generator Utilizing a Palladium-Based Hydrogen Combustion System - Grzegorz Mordarski; Konrad Skowron; Dorota Duraczyńska; Anna Drabczyk; Robert P. Socha (Energies)
The growing demand for sustainable energy solutions requires the development of safe and efficient systems for hydrogen utilization. Hydrogen, with its high energy density and clean combustion characteristics, has become a promising alternative for heating applications. However, conventional combustion technologies often suffer from inefficiencies and safety concerns, such as NOx emissions and explosion risks. To address these challenges, this study aimed to design and evaluate a catalytic heat generator utilizing hydrogen–air mixtures under controlled conditions to eliminate the need for pure oxygen and mitigate associated risks. A single-bed catalytic system was developed using palladium-based catalysts supported on ceramic fibers, followed by its heating, activation, and further characterization using the SEM-EDS technique. A multi-bed generator was later constructed to enhance scalability and performance. Thermal imaging and temperature monitoring were employed to optimize activation processes and assess system performance under varying hydrogen flow rates. The experimental results demonstrated efficient heat transfer and operational stability.